2016
DOI: 10.1038/srep30493
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement as a resource to distinguish orthogonal product states

Abstract: It is known that there are many sets of orthogonal product states which cannot be distinguished perfectly by local operations and classical communication (LOCC). However, these discussions have left the following open question: What entanglement resources are necessary and/or sufficient for this task to be possible with LOCC? In m ⊗ n, certain classes of unextendible product bases (UPB) which can be distinguished perfectly using entanglement as a resource, had been presented in 2008. In this paper, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…To distinguish a given nonlocal set, entanglement can be used as resource. There are several articles where entanglement in pure form was used to distinguish nonlocal sets [49,[53][54][55][56][57][58][59][60][61][62][63]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish a given nonlocal set, entanglement can be used as resource. There are several articles where entanglement in pure form was used to distinguish nonlocal sets [49,[53][54][55][56][57][58][59][60][61][62][63]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Another direction of research is to explore entanglement as a resource to distinguish quantum states of nonlocal sets [49][50][51][52][53][54][55][56][57][58] by LOCC. In particular, the problem of distinguishing product states of given nonlocal sets by LOCC using entanglement as a resource was considered in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[50], Cohen constructed entanglementassisted local protocols (protocols implementable by LOCC) to distinguish the orthogonal product states of several unextendible product bases. Later [56], separate entanglement-assisted local protocols were constructed to distinguish the states of a class of nonlocal bipartite COPBs. Recently [58], the problem of product state discrimination by LOCC was considered, where multiple copies of a maximally entangled state in C 2 ⊗C 2 are used as resource.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Zhang et al have shown that a C 2 ⊗ C 2 maximally entangled states is sufficient to perfectly distinguish certain classes by LOCC in C m ⊗C n [30] and have raised the question for a multipartite system. We believe that any class of locally indistinguishable orthogonal product states can be perfectly distinguished by LOCC with enough entanglements as resources.…”
Section: Introductionmentioning
confidence: 99%